Comet assay application for determining genotoxicity of veterinary vaccines preparations - Dybkova, S.M.; Roman'ko, M.E.; Gruzina, T.G.; Rieznichenko, L.S.; Ulberg, Z.R.; Ushkalov, V.O.; Golovko, A.M. (Вiopolymers and Cell, 2010)
Aim. To study a possibility of usage of the alkaline gel electrophoresis method (Comet assay) for determination of genotoxic properties of veterinary vaccines preparations. Methods. The alkaline gel electrophoresis of isolated eukaryotic cells has been used with further visualization of the samples by fluorescent microscopy. Results. Veterinary vaccines testing by the Comet assay method under alkaline conditions revealed that the samples No.1 and No 12 from twelve investigated vaccine preparations had genotoxic influence on eukaryotic cells of CHO-K1 and Vero test cultures, No. 12 sample being genotoxic only at metabolic activation. Conclusions. The method of alkaline gel electrophoresis of single cells (Comet assay) is suitable for determination of veterinary vaccines genotoxic influence on the test eukaryotic cells CHO-K1. The method proposed in this paper is express, inexpensive and predictive. The accompli-hed experimental work allows us to recommend this method for characterization of biosafety of veterinary vaccines preparations.